Exploring dupilumab for asthma: from mechanistic insights to clinical outcomes, safety, and cost-effectiveness - Ameer, Omar Z.; Mansour, Ghaith K.; Al-Amoudi, Raghad S.; Abu‐Owaimer, Fahmi M. (Frontiers in Pharmacology, 2025)
Type 2 (T2) inflammation underlies a substantial subset of moderate-to-severe asthma, contributing to persistent symptoms and frequent exacerbations. Dupilumab, a fully human immunoglobulin G subclass 4 (IgG4) monoclonal antibody, targets the interleukin-4 receptor alpha (IL-4Rα), thereby inhibiting both interleukin-4 (IL-4) and interleukin-13 (IL-13) signaling—which are key cytokines driving T2 inflammation. This review examines the formulation, pharmacological profile, clinical efficacy, safety, and cost-effectiveness of dupilumab in the treatment of asthma, with an emphasis on its role across T2-high and selected T2-low phenotypes. Dupilumab displays nonlinear pharmacokinetics, with approximately 61% bioavailability and a prolonged half-life that supports biweekly subcutaneous (SC) administration. Clinical trials have demonstrated significant reductions in asthma exacerbation rates, improvements in forced expiratory volume in one second (FEV1), and decreased oral corticosteroid (OCS) dependence in adults and children with moderate-to-severe asthma. The benefits are particularly robust in patients with elevated eosinophil counts or fractional exhaled nitric oxide (FeNO), although efficacy extends to some patients with T2-low profiles. Reported safety data show a favorable profile, with mild adverse events, such as injection-site reactions and nasopharyngitis, being the most common. Nonclinical studies using surrogate antibodies in animal models revealed no evidence of systemic toxicity, reproductive harm, or carcinogenicity, reinforcing the drug’s high therapeutic index. From a pharmacoeconomic perspective, dupilumab has been found to be cost-effective in Japan compared to other biologics such as benralizumab and mepolizumab for asthma treatment. It has also shown cost-effectiveness in countries such as South Korea and the United Kingdom, particularly among patients with frequent exacerbations or chronic OCS use. However, in settings such as the United States and Colombia, high drug acquisition costs limit its cost-effectiveness unless its use is restricted to high-risk populations. In summary, dupilumab provides a targeted and generally well-tolerated treatment option for severe asthma. It is approved as an add-on maintenance therapy for patients aged ≥6 years with moderate-to-severe asthma, particularly those with T2 inflammation. By maximizing clinical and economic benefits through precision-guided patient selection, dupilumab’s dual IL-4/IL-13 blockade makes it a versatile biologic—especially suited for T2-high and overlapping asthma phenotypes or patients with comorbidities such as nasal polyps, eosinophilic esophagitis, and atopic dermatitis.